Mixed copper(ii)-phenanthroline complexes induce cell death of ovarian cancer cells by evoking the unfolded protein response - Moráň, Lukáš; Pivetta, Tiziana; Masuri, Sebastiano; Vašíčková, Kateřina; Walter, Franziska; Prehn, Jochen; Elkalaf, Moustafa; Trnka, Jan; Havel, Josef; Vaňhara, Petr (Metallomics, 2019)
There is an ongoing need for the development of new cancer therapeutics that combine high cytotoxic efficiency with low side effects, and also override resistance to the first-line chemotherapeutics. Copper(ii)-phenanthroline complexes are promising compounds that were shown previously to induce an immediate cytotoxic response over a panel of tumor cell lines in vitro. The molecular mechanism, however, remained unresolved. In this work we performed a thorough study of the copper(ii)-phenanthroline complexes containing different imidazolidine-2-thione ligands in ovarian cancer cells, and revealed that these complexes induce endoplasmic reticulum (ER) stress and subsequently cell death mediated by the unfolded protein response. Alleviation of the ER-stress by tauroursodeoxycholic acid (TUDCA) attenuated the cytotoxic effects. In summary, we have identified a novel, ER-dependent, molecular mechanism mediating cytotoxic effects of copper(ii)-phenanthroline complexes.
Keywords: fenantroliny; komplexní sloučeniny; Coordination Complexes; měď; Copper; Humans; nádorové buněčné linie; lidé; Female; protinádorové látky; ženské pohlaví; Unfolded Protein Response; signální dráha UPR; Cell Line, Tumor; nádory vaječníků; Phenanthrolines; Antineoplastic Agents; Ovarian Neoplasms